2003
DOI: 10.1046/j.1540-8167.2003.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Versus Heart Rate Variability in Risk Prediction after Myocardial Infarction

Abstract: Heart Rate versus Heart Rate Variability. Introduction: The aim of this study was to evaluate and compare heart rate and heart rate variability (HRV) in risk prediction after acute myocardial infarction (MI) and to evaluate the effect of beta‐blocker treatment on the prognostic performance of heart rate and HRV. Methods and Results: Three hundred sixty‐six patients underwent 24‐hour Holter recording 1 to 6 days after an MI. HRV was expressed as the standard deviation of all normal‐to‐normal intervals. Left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 27 publications
(41 reference statements)
3
28
0
1
Order By: Relevance
“…First, the patients in this study were generally much older than the patients in the other studies and HRV decreases with increasing age [24]. Second, our patients had a higher resting HR, which also decreases HRV [25]. The HRV values are comparable to values obtained from other elderly patients [12].…”
Section: Discussionsupporting
confidence: 62%
“…First, the patients in this study were generally much older than the patients in the other studies and HRV decreases with increasing age [24]. Second, our patients had a higher resting HR, which also decreases HRV [25]. The HRV values are comparable to values obtained from other elderly patients [12].…”
Section: Discussionsupporting
confidence: 62%
“…Depressed HR variability is associated with the risk of life-threatening arrhythmias in patients after AMI (45). There is some suggestion that HR variability assessed very early after AMI may not add prognostic information beyond that of HR alone (46). However, others have shown that HR variability is strongly predictive after AMI (47,48), even when assessed during the first 7 days (49).…”
Section: Figure 5 Heart Rate Reduction and Mortality In Heart Failurementioning
confidence: 99%
“…Sin embargo, un estudio demostró que la variabilidad de la FC determinada por Holter no aportaba información adicional a la propia FC media 37 .…”
Section: Frecuencia Cardíaca Ambulatoriaunclassified